Challenges of Islamic Supervisory in The Islamic Financial Technology Industry - Rifqi Muhammad; Rima Lanaula (Economica: Jurnal Ekonomi Islam, 2019)
Abstract: Islamic financial industry is increasingly developing with the presence of financial technology both in the form of peer to peer lending and crowdfunding. Islamic financial technology (fintech) enables sharia business players to formulate financing schemes using innovative and diverse sharia contracts. This has become a challenge in the aspect of sharia supervision due to limited regulations, corporate governance, and human resource capabilities. This paper will discuss the development of the financial technology industry in Indonesia and specifically the development of Islamic financial technology in terms of the growth in the number of service providers, the amount of financing, regulation and corporate governance. Secondly, this paper will discuss the challenges faced in the field of sharia compliance and the role of the sharia supervisory board in sharia supervision. Third, this paper will formulate corporate governance and human resource competencies of sharia supervisory board to encourage sharia compliance. Finally, this paper will formulate the conclusions and recommendations for improving regulation of the financial technology industry.Abstrak: Industri keuangan syariah semakin diramaikan dengan munculnya teknologi finansial (financial technology) baik yang berbentuk peer to peer lending maupun crowdfunding. Islamic financial technology (fintech) memungkinkan para pelaku bisnis syariah untuk merumuskan skema pembiayaan menggunakan akad-akad syariah yang semakin inovatif dan beragam. Hal ini menjadi tantangan dalam aspek pengawasan syariah karena keterbatasan regulasi, tata kelola perusahaan (corporate governance), dan kemampuan sumber daya manusia. Paper ini akan membahas perkembangan industri teknologi finansial di Indonesia dan secara khusus perkembangan Islamic financial technology dari sisi pertumbuhan jumlah penyedia jasa, jumlah pembiayaan, regulasi maupun tata kelola perusahaan. Kedua, paper ini membahas tantangan yang dihadapi dalam bidang kepatuhan syariah dan peran DPS (Dewan Pengawas Syariah) dalam pengawasan syariah. Ketiga, paper ini merumuskan tata kelola perusahaan dan kompetensi sumber daya manusia DPS untuk mendorong kepatuhan syariah Islamic financial technology. Akhirnya, paper ini merumuskan kesimpulan dan rekomendasi untuk perbaikan regulasi industri teknologi finansial.